2021
DOI: 10.3390/ijms22063084
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Butyrate Induced Regulation of T Cell Surface Expression of CTLA-4 in Patients with Ulcerative Colitis

Abstract: Patients with ulcerative colitis (UC) have reduced intestinal levels of short-chain fatty acids (SCFAs), including butyrate, which are important regulators of host–microbiota crosstalk. The aim was therefore to determine effects of butyrate on blood and intestinal T cells from patients with active UC. T cells from UC patients and healthy subjects were polyclonally stimulated together with SCFAs and proliferation, activation, cytokine secretion, and surface expression of cytotoxic T lymphocyte-associated antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Propionic acid reduces inflammation by inhibiting the expression of chemokines and cytokines and regulating the activation of neutrophils (Chang et al., 2014). Butyrate is an important energy source for intestinal epithelial cells, which has the ability to regulate the growth of epithelial cells and immune response and repair intestinal mucosal injury (Magnusson et al., 2021). The results of MPEA analysis showed that HLP had a significant regulatory effect on propanoate metabolism and butanoate metabolism pathway ( p < .05).…”
Section: Resultsmentioning
confidence: 99%
“…Propionic acid reduces inflammation by inhibiting the expression of chemokines and cytokines and regulating the activation of neutrophils (Chang et al., 2014). Butyrate is an important energy source for intestinal epithelial cells, which has the ability to regulate the growth of epithelial cells and immune response and repair intestinal mucosal injury (Magnusson et al., 2021). The results of MPEA analysis showed that HLP had a significant regulatory effect on propanoate metabolism and butanoate metabolism pathway ( p < .05).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the level of CTLA4 expression in UC remains unclear. Wang et al 58 and Magnusson et al 59 suggested that CTLA4 expression in T cells was lower in UC patients than in healthy individuals. However, other studies have shown that CTLA4 mRNA expression was significantly higher in colonic mucosal tissue from patients with active UC compared with controls devoid of inflammation 60 .…”
Section: Discussionmentioning
confidence: 99%
“…The immune checkpoint genes evaluated included CD274, also known as PD-L1, that encodes an immune inhibitory ligand expressed by hematopoietic and nonhematopoietic cells such as T cells and various tumor cells [ 39 ]. CTLA4, a member of the immunoglobulin superfamily, encodes a protein that transmits an inhibitory signal to T cells [ 40 ]. HAVCR2 or TIM3 is a cell surface marker expressed on CD8+ Th1 and CD4+ Th1 cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%